2012
DOI: 10.1007/s00227-012-1879-8
|View full text |Cite
|
Sign up to set email alerts
|

Particle sorting and formation and elimination of pseudofaeces in the bivalves Mulinia edulis (siphonate) and Mytilus chilensis (asiphonate)

Abstract: Mulinia edulis and Mytilus chilensis are suspension-feeding bivalves with homorhabdic gills that live in diVerent sedimentary habitats in the lower and upper intertidal, respectively, in Yaldad Bay, Chile. They are faced with diVerent suspended particle size distributions when feeding, and both eliminate most of the inorganic particles by pseudofaeces production. This study used histology, scanning and transmission electron microscopy, and video endoscopy to compare particle processing on the labial palps and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…There is evidence for such a gateway role for benthic fauna: Tait et al (2015) found that rapid removal of phytodetritus from the surface sediment at L4 is driven by macrofaunal consumption, and that organic material available for bacterial degradation within sediments is first processed by macrofauna. Moreover, some suspension feeder taxa produce pseudofaeces (Garrido et al, 2012), which is effectively another pathway dedicated to conversion of suspended matter into benthic deposits. The concept of suspension feeders having preferential access to pelagic food sources is not surprising and has been previously applied in modelling studies (e.g., Maar and Hansen, 2011); however, in those it was prescribed by the model structure rather than emerging as a result of model calibration, as is the case here.…”
Section: On the Response Of Deposit And Suspension Feeders To Food Avmentioning
confidence: 99%
“…There is evidence for such a gateway role for benthic fauna: Tait et al (2015) found that rapid removal of phytodetritus from the surface sediment at L4 is driven by macrofaunal consumption, and that organic material available for bacterial degradation within sediments is first processed by macrofauna. Moreover, some suspension feeder taxa produce pseudofaeces (Garrido et al, 2012), which is effectively another pathway dedicated to conversion of suspended matter into benthic deposits. The concept of suspension feeders having preferential access to pelagic food sources is not surprising and has been previously applied in modelling studies (e.g., Maar and Hansen, 2011); however, in those it was prescribed by the model structure rather than emerging as a result of model calibration, as is the case here.…”
Section: On the Response Of Deposit And Suspension Feeders To Food Avmentioning
confidence: 99%
“…Some studies show that it depends on particles' characteristics such as size, shape, and surface properties, which affect their ingestion or rejection [29,30]. The rejected particles are bound to cohesive mucus, deposited in speci c places in the mantle and then transported to the cilia, for their expulsion as pseudofeces [31]. Additionally, the mucus covering feeding organs can mediate particles selection [13].…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, other factors will influence whether a particle will enter the principal filaments (see below), such as the shape of the particle (e.g., long thin cells and fibers) and muscular movements of the gill, which affect the distance between adjacent plicae. Similar anatomical constraints exist for the labial palps, where, in many species, some particles are transported on the crests of the ridges both proximally and anteriorly, and others become trapped in the troughs between ridges and are carried distally to the edge of the palp for rejection as pseudofeces (Galtsoff 1964;Beninger and St-Jean 1997;Garrido et al 2012). Finally, the mouth of the bivalve also constrains the upper size limit of particles that can be ingested.…”
Section: Particle Selectionmentioning
confidence: 91%
“…Although the exact mechanisms of selection are still being resolved, it is known that particle size, shape, and surface properties (both specific and non-specific) affect preferential rejection and ingestion of material (see Ward and Shumway 2004;Rosa et al 2018). Particles destined for rejection are bound in cohesive mucus, transported via well-developed mucociliary processes to specific sites on the mantle, and expelled as pseudofeces (Galtsoff 1964;Ward et al 1994;Beninger and St-Jean 1997;Garrido et al 2012). The loci of selection are speciesspecific, and depend upon the architecture and ciliary tracts of the gill.…”
Section: Particle Selectionmentioning
confidence: 99%